Chemical Bonding in Homoleptic Carbonyl Cations [M{Fe(CO)5}2]+ (M=Cu, Ag, Au). Issue 23 (16th March 2021) - Pan, Sudip; Gorantla, Sai Manoj N. V. T.; Parasar, Devaborniny; Dias, H. V. Rasika; Frenking, Gernot
Abstract: Syntheses of the copper and gold complexes [Cu{Fe(CO)5 }2 ][SbF6 ] and [Au{Fe(CO)5 }2 ][HOB{3, 5‐(CF3 )2 C6 H3 }3 ] containing the homoleptic carbonyl cations [M{Fe(CO)5 }2 ] + (M=Cu, Au) are reported. Structural data of the rare, trimetallic Cu2 Fe, Ag2 Fe and Au2 Fe complexes [Cu{Fe(CO)5 }2 ][SbF6 ], [Ag{Fe(CO)5 }2 ][SbF6 ] and [Au{Fe(CO)5 }2 ][HOB{3, 5‐(CF3 )2 C6 H3 }3 ] are also given. The silver and gold cations [M{Fe(CO)5 }2 ] + (M=Ag, Au) possess a nearly linear Fe‐M‐Fe' moiety but the Fe‐Cu‐Fe' in [Cu{Fe(CO)5 }2 ][SbF6 ] exhibits a significant bending angle of 147° due to the strong interaction with the [SbF6 ] − anion. The Fe(CO)5 ligands adopt a distorted square‐pyramidal geometry in the cations [M{Fe(CO)5 }2 ] +, with the basal CO groups inclined towards M. The geometry optimization with DFT methods of the cations [M{Fe(CO)5 }2 ] + (M=Cu, Ag, Au) gives equilibrium structures with linear Fe‐M‐Fe' fragments and D 2 symmetry for the copper and silver cations and D 4 d symmetry for the gold cation. There is nearly free rotation of the Fe(CO)5 ligands around the Fe‐M‐Fe' axis. The calculated bond dissociation energies for the loss of both Fe(CO)5 ligands from the cations [M{Fe(CO)5 }2 ] + show the order M=Au ( D e =137.2 kcal mol −1 )>Cu ( D e =109.0 kcal mol −1 )>Ag ( D e =92.4 kcal mol −1 ). The QTAIM analysis shows bond paths and bond critical points for the M−Fe linkage but not between M and the CO ligands. The EDA‐NOCV calculations suggest that the [Fe(CO)5 ]→M + ←[Fe(CO)5 ] donation is significantly stronger than the [Fe(CO)5 ]←M + →[Fe(CO)5 ] backdonation. Inspection of the pairwise orbital interactions identifies four contributions for the charge donation of the Fe(CO)5 ligands into the vacant ( n )s and ( n )p AOs of M + and five components for the backdonation from the occupied (n‐1)d AOs of M + into vacant ligand orbitals. Abstract : Donation of an electron pair from the HOMO of [Fe(CO)5 ]2 to the 4s LUMO of Cu + giving the (+, +) component of the Fe‐Cu‐Fe σ bond in [Cu{Fe(CO)5 }2 ] + . The associated charge flow with the direction red→blue is given by the deformation density.